Preventive and Therapeutic Strategies for Gestational Diabetes: A Literature Review - Apryanti, Yohana Putri; Astuti, Siti Choirul Dwi (Ahmar Metastasis Health Journal, 2025)
Gestational diabetes is a glucose intolerance disorder that arises during pregnancy and is one of the most common obstetric complications globally. Its increasing prevalence is closely linked to high rates of obesity, unhealthy dietary patterns, physical inactivity, and advanced maternal age, particularly in developing countries like Indonesia, which still face limitations in screening and maternal healthcare services. This condition has both short-term and long-term impacts, including an increased risk of type 2 diabetes in both mothers and their children. This article presents a systematic literature review of preventive and therapeutic strategies for managing gestational diabetes, evaluating their effectiveness and potential for implementation. The method employed is a qualitative descriptive literature review, based on scientific articles from the past decade, obtained from databases such as PubMed, Scopus, and Garuda. The review findings indicate that the most effective preventive strategy is lifestyle modification, such as adopting a healthy diet and engaging in light physical activity, especially when implemented early in pregnancy or even before conception, which can reduce the risk of gestational diabetes by up to 25%. Therapeutic strategies include medical nutrition therapy, the use of insulin or metformin, self-monitoring of blood glucose, as well as education and psychosocial support. The use of digital technologies, including mobile applications and telehealth services, has also been shown to improve patient adherence and engagement. A holistic approach that integrates both preventive and therapeutic efforts continuously is considered the most effective in reducing complications and long-term risks. However, challenges such as limited access to healthcare services, low health literacy, and a shortage of trained healthcare personnel remain obstacles in Indonesia. Therefore, cross-sector collaboration among healthcare professionals, families, and policymakers is crucial to optimize the contextual and sustainable management of gestational diabetes.